2022
DOI: 10.1029/2022ja030456
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Density Oscillations Associated With Recurrent Prompt Penetration Electric Fields During the Space Weather Event of 4 November 2021 Over the East‐Asian Sector

Abstract: We found the signatures of the multiple prompt penetration electric fields and the disturbance dynamo electric field having impacts on the East Asian sector ionosphere along the meridional chain thoroughly from the equator, low‐mid to high latitudes during the space weather event of 3–5 November 2021. The observation is made on global positioning system‐total electron content (GPS‐TEC), digisonde, and magnetometer stations. In the main phase of the storm, intense modulations of vertical total electron content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
(185 reference statements)
0
1
0
Order By: Relevance
“…We refer to this as the interplanetary electric field extending from dawn to dusk (IEFy), and we are actually calculating it using the formula V x Bz. Some studies have shown that during such events, a strong dawn-to-dusk electric field envelopes the entire Earth, triggering the Prompt Penetration of Electric Fields (PPEF) phenomenon almost instantly (Singh et al, 2022;Idosa & Shogile, 2023).…”
Section: Responses Of Near-earth Space Environmentmentioning
confidence: 99%
“…We refer to this as the interplanetary electric field extending from dawn to dusk (IEFy), and we are actually calculating it using the formula V x Bz. Some studies have shown that during such events, a strong dawn-to-dusk electric field envelopes the entire Earth, triggering the Prompt Penetration of Electric Fields (PPEF) phenomenon almost instantly (Singh et al, 2022;Idosa & Shogile, 2023).…”
Section: Responses Of Near-earth Space Environmentmentioning
confidence: 99%